ACOG Committee Opinion No. 804: physical activity and exercise during pregnancy and the postpartum period - Mota, Patrícia (2021)
It was a great pleasure to read the Committee Opinion on physical activity and exercise during pregnancy and the postpartum period in the April 2020 issue. The recommendations were clear, and this document is of great use for physicians, physiotherapists, midwives, exercise scientists, coaches, and other professionals working with pregnant and postpartum women.